Vitamin D, Homocysteine, and Thyroid Dysfunction as Risk Factors for Missed Abortion: A Retrospective Risk Factor Analysis - Fang Q; Sang L; Du S; Wang R; Wu H; Yang L; Yu J (International Journal of Women's Health)
Qianjin Fang, Lin Sang, Shihua Du, Runqiu Wang, Haihong Wu, Lu Yang, Jie Yu Department of Obstetrics and Gynecology, The Second People’s Hospital of Hefei, Hefei Hospital Affiliated to Anhui Medical University, Hefei, Anhui Province, 230011, People’s Republic of ChinaCorrespondence: Qianjin Fang, Department of Obstetrics and Gynecology, The Second People’s Hospital of Hefei, Hefei Hospital Affiliated to Anhui Medical University, Hefei, Anhui Province, 230011, People’s Republic of China, Email qianjinfang_fqj@126.comObjective: This study aimed to identify potential associations between missed abortion (MA) and risk factors, including low levels of vitamin D, high homocysteine, and abnormal thyroid function, among women undergoing early pregnancy assessments, thereby bridging the clinical knowledge gap regarding modifiable risk factors for MA.Methods: This retrospective study analyzed serum levels of vitamin D, (25-(OH)-D3), homocysteine (Hcy), and thyroid hormones (thyroid-stimulating hormone [TSH], thyroid peroxidase antibodies [TPOAb]) in 158 women who experienced missed abortion compared to 237 women with normal early pregnancy outcomes.Results: MA patients had significantly lower vitamin D levels (P = 0.04), higher Hcy (P < 0.05), and evidence of abnormal thyroid function, including TSH levels ≥ 4 mIU/L (P = 0.01) and positive TPOAb (P = 0.02). Low vitamin D was significantly associated with an increased risk of MA (odds ratio = 1.8; P = 0.03).Conclusion: These findings suggest that low vitamin D levels may be a potential risk factor for MA, highlighting the importance of monitoring and supplementation in early pregnancy to reduce the risk of missed abortion. As this study is retrospective, it cannot establish causality between the identified factors and MA.Keywords: missed abortion, vitamin D, homocysteine, thyroid function, risk factors